Thermal simulation of flexible LED package enhanced with copper pillars - 刘洋 梁润园 黄洁莹 袁长安 张国旗 孙凤莲 (Journal of semiconductors, 2015)
Chip on flexible substrate （COF） is a new packaging technology for light emitting diodes （LED）. This paper investigated the effect of Cu-pillar in the polyimide （PI） layer on the thermal properties of COF LED pack- ages by finite element analysis. The thermal distribution and thermal resistance were studied in both COF LED packages with and without Cu-pillar. The PI layer showed the highest thermal resistance in the typical package and led to a high chip temperature. With the addition of Cu-pillars, however, the thermal resistance of the PI layer sig- nificantly decreased due to the improvement of vertical thermal dissipation under LED chips. Based on the results of simulation and calculation, the relationship between the amount of Cu-pillar and thermal resistance of the COF package has been built. For the packages studied in this research, an 8 × 8 Cu-pillars array was adequate to improve the thermal performance of COF packages.